Variations in the path of the inferior alveolar canal. Review of the literature. (International Journal of Medical and Surgical Sciences, 2017)
The knowledge and application of anatomy is essential for any professional involved in the evaluation, diagnosis, prognosis and treatment of the different alterations of the maxillofacial complex. The ignorance of the anatomical relationships of the inferior alveolar duct in the different surgical procedures can lacerate, compress or stretch the nerve generating lesions such as neuropraxia, axonotmesis and neurotmesis. The objective of this review is to describe the variations of the inferior alveolar duct course reported in the literature. There are 6 possible categories in which the variations of the CAI can be classified: 4 views in panoramic radiographs (two dimensions) and 2 views in computerized axial tomography (three dimensions). The inferior alveolar duct presents a great variability between patients and populations, which accentuate the product of tooth loss and alveolar reabsorption. Computed tomography of conic beam is the most suitable method for its evaluation.
Keywords: inferior alveolar conduct; cone beam computed tomography; inferior alveolar nerve